Latin American literatures in global markets : the world inside - Moraña, Mabel; Gallego Cuiñas, Ana (Brill, 2023)
"Market relations are changing not only the distribution and promotion of literary works but also their content, their language, and their social and political function. This book penetrates the intricacies of literary production, circulation and reception, focusing on some of the most original and representative authors of today such as Roberto Bolaño, Gabriela Cabezón Camara, Yuri Herrera, and Irmgard Emmelhainz, among others. The book also illuminates on the "materialitity" of literature and the strategies of literary marketing: festivals, book fairs, digitalization, and translation. Globalization and regional particularisms meet, then, in the symbolic territories of the literary world, and expose their dynamics and intrinsic negotiations"-- Provided by publisher.
Keywords: Latin American literature -- 20th century -- History and criticism.; Latin American literature -- 21st century -- History and criticism.; Literature publishing -- Latin America.; Littérature latino-américaine -- 20e siècle -- Histoire et critique.; Littérature latino-américaine -- 21e siècle -- Histoire et critique.; Littérature -- Édition -- Amérique latine.; Latin American literature; Literature publishing; Latin America; 1900-2099; Criticism, interpretation, etc.; Essays; Literary criticism; Literary criticism.; Essays.; Critiques littéraires.